Processing and Characterization of a Polypropylene Biocomposite Compounded with Maleated and Acrylated Compatibilizers - Brent A. Nerenz; Michael A. Fuqua; Venkata S. Chevali; Chad A. Ulven (International Journal of Polymer Science)
Polypropylene (PP) biocomposites containing 20 wt.% sunflower hull as a particulate reinforcement were compounded and tested under tensile, flexural, and impact loadings. The incorporation of the sunflower hull without compatibilizer resulted in diminished tensile strength and impact energy absorption but increased flexural strength and both tensile modulus and flexural modulus when compared to neat PP. Formulations containing three different chemical compatibilizers were tested to determine their effectiveness in improving the interfacial adhesion between the fiber surface and PP chains. Maleic anhydride grafted with PP (MA-g-PP) achieved greater improvements in tensile strength but reduced impact strength in comparison to an acrylic-acid-grafted PP compatibilizer (AA-g-PP). The molecular weight, graft level, and the ability to affect strength, modulus, and absorbed impact energy were also investigated for the compatibilizers. A MA-g-PP having high molecular weight and low graft level was most effective in improving the investigated properties of a sunflower hull-reinforced polypropylene biocomposite.